User language and cultural product innovation: insights from the global mobile gaming industry - Zhang, Pengxiang; Yi, Jingtao; Niu, Chao; Zhao, Eric Yanfei; Li, Sali (Journal of International Business Studies, 2025)
Traditional studies on cultural industries have emphasized localized innovation rooted in cultural products’ countries of origin. While this research acknowledges the significance of production origin, the digital transformation of cultural industries has shifted the landscape of cultural product innovation from traditional localized processes to a more globalized and democratic approach by engaging users worldwide. However, there is a notable gap in understanding demand-side variations in users from different countries, particularly as digitalization allows global users’ languages to convey diverse linguistic inputs. To address this gap, we investigate how users’ future-time reference (FTR) across countries influences the pace of cultural product innovation in the mobile gaming industry. Analyzing a global sample of 7787 mobile games, we find that in countries where gamers predominantly use weak FTR languages, their communication exhibits proximate temporal framing, prompting the introduction of new gaming content at a faster pace. Further, the effectiveness of such FTR framing becomes more pronounced when publishers pay close attention to or are familiar with gamers’ languages. These findings contribute important insights for research on country of origin and cultural industries and for managers to better engage users to drive cultural product innovation.